Long-Term Effects of COVID-19 on Chronic Obstructive Pulmonary Disease - Lee CT; Wang PH; Cheng SL (International Journal of COPD)
Chi-Tai Lee,1 Ping-Huai Wang,1– 3 Shih-Lung Cheng1,4 1Division of Pulmonology, Department of Internal Medicine, Far Eastern Memorial Hospital, New Taipei City, Taiwan; 2Department of Nursing, Asia Eastern University of Science and Technology, New Taipei City, Taiwan; 3School of Medicine, National Yang Ming Chiao Tung University, Taipei City, Taiwan; 4Department of Chemical Engineering and Materials Science, Yuan-Ze University, Tauyuan City, TaiwanCorrespondence: Ping-Huai Wang, Division of Pulmonology, Department of Internal Medicine, Far Eastern Memorial Hospital, 21 Sec 2 Nan-Ya South Road, Banchiao Distinct, New Taipei City, 220, Taiwan, Tel +886277281815, Email pinghuaiwang@gmail.comBackground: Research has demonstrated that chronic obstructive pulmonary disease (COPD) is a negative prognostic factor for patients with the coronavirus disease 2019 (COVID-19). The long-term complications of COVID-19 among patients with COPD remain poorly understood due to limited studies.Methods: This retrospective study included patients with COPD who underwent regular follow-ups in a medical center between January 1, 2020, and December 31, 2022. The patients were categorized into COVID-19 and non-COVID-19 groups. Comparative analyses were conducted to assess clinical demographics, characteristics, acute exacerbations of COPD (AECOPD), and survival rates between the two groups. Subgroup analysis was performed based on inpatient and outpatient status within the COVID-19 group.Results: Of the 696 patients with COPD, 86 (12.4%) were included in the COVID-19 group, while 610 (87.6%) were included in the non-COVID-19 group. Patients in the COVID-19 group were significantly older (age: 75.0 ± 8.8 years versus 72.0 ± 9.0 years, p = 0.004), exhibited higher mortality rates (4.6% versus 0%, p < 0.001), and increased annual times of AECOPD (0.17 versus 0.08, p = 0.018) than those in the non-COVID-19 group after COVID-19. Multivariate analysis revealed that COVID-19 infection is an independent risk factor for increased AECOPD incidence (adjusted odds ratio: 1.74; 95% confidence interval [CI]: 1.07– 2.83, p = 0.024). Within the COVID-19 group, the inpatient subgroup exhibited a higher prevalence of heart failure comorbidity (20% versus 2.8%, p = 0.035) and lower forced vital capacity than the outpatient subgroup (2.03 ± 0.60 L versus 2.56 ± 0.72 L, p = 0.016).Conclusion: Age is a significant risk factor for COVID-19 infection among patients with COPD. After COVID-19, these patients exhibit an increased frequency of severe exacerbations and a high risk of mortality. Notably, the susceptibility to severe exacerbations persists regardless of whether the patients receive inpatient or outpatient care.Keywords: Coronavirus disease, COVID-19, SARS-CoV-2, COPD, outcome